2006
DOI: 10.1037/cjbs2006018
|View full text |Cite
|
Sign up to set email alerts
|

Construction d'une échelle d'attachement au lieu de travail: Une démarche exploratoire.

Abstract: Notre article présente les résultats d'une série de cinq études visant la construction et la validation d'une échelle d'attachement au lieu de travail (ÉALT). S'appuyant sur la Théorie de l'attachement au lieu (Place attachment) définie par Shumaker et Taylor (1983) et concevant l'attachement au lieu de travail comme un lien affectif résultant de l'interaction dynamique entre une personne et son environnement de travail, cette mesure est une adaptation au monde professionnel de la Neighborhood Attachment Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 59 publications
1
29
0
5
Order By: Relevance
“…Convergent validity analyses were conducted by calculating correlation coeffi cients between the three styles of attachment in the workplace, aff ective commitment ( Allen & Meyer, 1990 ), and workplace attachment ( Rioux, 2006 ). The correlations show that the three constructs in question can be considered distinct, since the correlations were signifi cant, but weak to moderate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Convergent validity analyses were conducted by calculating correlation coeffi cients between the three styles of attachment in the workplace, aff ective commitment ( Allen & Meyer, 1990 ), and workplace attachment ( Rioux, 2006 ). The correlations show that the three constructs in question can be considered distinct, since the correlations were signifi cant, but weak to moderate.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace attachment .-To assess workplace attachment, the EALT (échelle d'attachement au lieu de travail) validated by Rioux (2006 ) was used. This one-dimensional scale has six items (e.g., "This workplace is part of myself"), rated on a seven-point Likert-type response scale with anchors 1: Strongly disagree and 7: Strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…Workplace attachment is defined as the affective bond resulting from the dynamic interaction between a person and his/her organizational environment (Rioux, 2006a) and is considered to be an important aspect of the quality of work life. Several studies (e.g., Dinç, 2010) have shown that when employees are able to customize their workplace, they are more attached to it, and this raises the indices of the quality of work life such as job satisfaction, wellbeing and performance.…”
Section: The Workplace Attachment and The Workplace Attachment Stylesmentioning
confidence: 99%
“…To assess workplace attachment, we used the Work Attachment Scale (EALT/WAS) validated by Rioux (2006a). This is a one-dimensional scale consisting of seven items (i.e.…”
Section: Instrumentsmentioning
confidence: 99%
“……that allows you to make decisions (Autonomy). We chose Rioux's (2006) scale of workplace attachment (Echelle d'Attachement au Lieu de Travail -EALT), which was based on work by Altman and Ginat (1992). Altman and Ginat considered that attachment can have different, but equally important, definitions depending on whether the aim is to analyze the consequences related to feelings aroused by the environment or the social and psychological processes that occur between a person and his or her environment-in other words, the reasons for the attachment.…”
Section: Items To Identify the Places Perceived As Giving Meaning To mentioning
confidence: 99%